Affinity Bioorthogonal Chemistry (ABC) Tags for Site‐Selective Conjugation, On‐Resin Protein‐Protein Coupling, and Purification of Protein Conjugates. (7th October 2022) - Scinto, Samuel L.; Reagle, Tyler R.; Fox, Joseph M.
Abstract: The site‐selective functionalization of proteins has broad application in chemical biology, but can be limited when mixtures result from incomplete conversion or the formation of protein containing side products. It is shown here that when proteins are covalently tagged with pyridyl‐tetrazines, the nickel‐iminodiacetate (Ni‐IDA) resins commonly used for His‐tags can be directly used for protein affinity purification. These Affinity Bioorthogonal Chemistry (ABC) tags serve a dual role by enabling affinity‐based protein purification while maintaining rapid kinetics in bioorthogonal reactions. ABC‐tagging works with a range of site‐selective bioconjugation methods with proteins tagged at the C‐terminus, N‐terminus or at internal positions. ABC‐tagged proteins can also be purified from complex mixtures including cell lysate. The combination of site‐selective conjugation and clean‐up with ABC‐tagged proteins also allows for facile on‐resin reactions to provide protein‐protein conjugates. Abstract : Affinity Bioorthogonal Chemistry tags (ABC‐tags) based on 2‐pyridyltetrazines serve a dual role by enabling protein purification through metal chelation and still maintaining their rapid kinetics in bioorthogonal reactions. ABC‐tagging is successful for proteins tagged at the C‐ or N‐terminus or at internal positions, is successful in complex mixtures including cell lysate, and can be carried out on‐resin to generate multidomain proteins.